Double-lumen catheter in the right jugular vein induces two sub-endothelial abscesses in an unusual place, the transition between the superior vena cava and the right atrium: A case report - Lima, João Kennedy Teixeira; Lima, Sylvia Rannyelle Teixeira; De Lima, Antonio Leonel; Agra, Cícero Valdizébio Pereira; Valenti, Vitor Engrácia [UNESP]; Gomes, Rayana Loch [UNESP]; Rodrigues, Luciano Miller; Correa, João Antonio; Raimundo, Rodrigo D.; De Abreu, Luiz Carlos (Springer Nature, 2014)
Endocarditis is a type of infection that is common in internal medicine wards and in haemodialysis clinics. The location that is most affected are the heart valves. Herein, we report a case of an uncommon abscess, a sub-endothelial abscess between the transition of the superior vena cava and the right atrium. There were several emboli to the lung and foot, and the agent was related to Staphylococcus aureus and a double-lumen catheter. Usually, this type of abscess is located in valves, either the tricuspid valve if related to catheters or injection drug use or the mitral valve if related to other causes. An exhaustive review was made, but we found no information about the location of this abscess and the rarity of the event motivating the report of infection.
Keywords: Central venous catheters; Endocarditis; Hospitalisation; Renal dialysis